2008
DOI: 10.5194/angeo-26-3933-2008
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength dependence of the <I>E<sub>s</sub></I> layer instability, and of coupling to the F layer, in the nonlinear regime

Abstract: Abstract. The E s layer instability has been suggested as a participant in the creation of frontal structures observed in both the E s and F layers of the nighttime midlatitude ionosphere, in spite of the fact that the spatial scales of the frontal structures are very different in the two layers. The linear growth rate of the instability has a maxima in the vicinity of the wavelength observed for the E s layer structures (short wavelengths). However, the maxima is non-distinct, and simulations have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It seems that many previous results must be affected by many authors. This author intends to begin by reconsidering E-F coupling effects in a number of his previous works Cosgrove, 2007aCosgrove, , 2007bCosgrove, , 2008and Cosgrove, 2013] and by reanalyzing the IFI. Also, we intend to perform ionospheric…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…It seems that many previous results must be affected by many authors. This author intends to begin by reconsidering E-F coupling effects in a number of his previous works Cosgrove, 2007aCosgrove, , 2007bCosgrove, , 2008and Cosgrove, 2013] and by reanalyzing the IFI. Also, we intend to perform ionospheric…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…The short wavelength cutoff occurs at around 20 km because the wavelength becomes comparable to the layer thickness, and the growth rate gradually decreases at longer wavelengths mode due to the F layer loading effect. Cosgrove [] studied the E‐F coupled instability by two‐dimensional simulation and showed that longer wavelengths grew to larger amplitude because of a longer interaction time between the two regions. Although several aspects given by the above‐mentioned studies are consistent with the observations, they could not quantitatively explain the preferable wavelength of MSTIDs.…”
Section: Introductionmentioning
confidence: 99%